Delayed physical development in a first generation enslaved African woman from Pietermaai, Curaçao - Fricke, Felicia; Laffoon, Jason; Victorina, Amy; Haviser, Jay (International journal of osteoarchaeology, 2020)
There is still much to be learned about enslavement in Curaçao, where little archaeological investigation into the historical era has been carried out. This article contributes to our knowledge on this subject through the analysis of a female individual buried in Pietermaai, an 18th century suburb of Willemstad. Excavated in the 1980s by the Archaeological‐Anthropological Institute of the Netherlands Antilles, the remains are only now attracting osteological attention. Isotopic analysis has shown that this individual spent her childhood in West Africa, supporting morphological and metric analyses identifying her African ancestry. At the time of death, she had an adult chronological age (over 18 years), but her physical development indicated a non‐adult biological age (possibly between 12 and 15 years). Such delayed development can occur due to many factors, including hard labour and disease. In the case of this individual, evidence such as enamel hypoplasia, osteochondritis dissecans, and periostitis may indicate stressful episodes throughout the life course. Clearly defined entheses and entheseal changes at muscle attachment sites on the arms and legs may indicate a physically demanding occupation. A variety of factors could therefore have contributed to her developmental delay. In the future, further analysis of buried populations in Curaçao will help to increase our understanding of the lifeways of enslaved people here. Meanwhile, the analysis of this isolated individual is important because it situates enslavement in a real body and indicates the value of reanalysis of human remains from existing archaeological collections in the Caribbean.